Examples of the Simplest Exercises with Synonyms and Subject and Predicate - Alimova Namuna Numanovna (Researchparks Publishing, 2022)
The work on the sentence occupies a central place in language teaching also because the assimilation of morphology and vocabulary, phonetics and spelling is carried out on a syntactic basis. The vocabulary of the native language is also mastered by students on the basis of a sentence. The lexical meaning of a word and the peculiarities of its use are revealed in a phrase or in a sentence. The meaning of the word is specified in the sentence. In context , the word is always.